2007
DOI: 10.1371/journal.pone.0000352
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing Shows that European Isolates of Francisella tularensis Subspecies tularensis Are Almost Identical to US Laboratory Strain Schu S4

Abstract: Background Francisella tularensis causes tularaemia, a life-threatening zoonosis, and has potential as a biowarfare agent. F. tularensis subsp. tularensis, which causes the most severe form of tularaemia, is usually confined to North America. However, a handful of isolates from this subspecies was obtained in the 1980s from ticks and mites from Slovakia and Austria. Our aim was to uncover the origins of these enigmatic European isolates.Methodology/Principal FindingsWe determined the complete genome sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 33 publications
1
31
0
4
Order By: Relevance
“…The two Slovakian isolates clustered with the highly pathogenic laboratory strain Schu4. The isolate FSC198 was finally sequenced completely and found to be almost identical to the laboratory strain Schu4 (6). A comparison of mutation patterns of an isolate propagated from Schu4 in vitro (FSC043) and FSC198 indicated that FSC198 diverged from its progenitor Schu4 and has subsequently passed life-cycles in a natural environment (36).…”
Section: Tularemiamentioning
confidence: 99%
“…The two Slovakian isolates clustered with the highly pathogenic laboratory strain Schu4. The isolate FSC198 was finally sequenced completely and found to be almost identical to the laboratory strain Schu4 (6). A comparison of mutation patterns of an isolate propagated from Schu4 in vitro (FSC043) and FSC198 indicated that FSC198 diverged from its progenitor Schu4 and has subsequently passed life-cycles in a natural environment (36).…”
Section: Tularemiamentioning
confidence: 99%
“…Individual feature gain events are represented by light gray arrows, and individual feature loss events are represented by black arrows. and two subsequent sequencing projects showed that it exhibits little genomic diversity (Beckstrom-Sternberg et al 2007;Chaudhuri et al 2007). Subspecies holarctica is a highly infectious but rarely fatal lineage (Ellis et al 2002), of which three strains have been sequenced (Petrosino et al 2006 Scheuermann, et al, unpubl.).…”
Section: Application To Francisella Turalensismentioning
confidence: 99%
“…tularensis, die bei Bratislava in der Slowakei und im Südosten Ös-terreichs u.a. aus Zecken isoliert wurden, um Bakterien handelt, die mit dem Laborstamm Schu S4 aus den USA nahezu identisch sind und von ihm abstammen dürften [28]. Eine konkrete Erklärung dafür konnte nicht gegeben werden.…”
Section: Francisella Tularensisunclassified